2007
DOI: 10.1007/s10238-007-0140-0
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol dehydrogenase (ADH) isoenzymes and aldehyde dehydrogenase (ALDH) activity in the sera of patients with colorectal cancer

Abstract: Various isoenzymes of alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) exist in human colorectal mucosa. In our last experiments we have shown that ADH and ALDH are present also in colorectal cancer cells. Moreover the activities of total ADH and class I isoenzymes were significantly higher in cancer tissue than healthy mucosa. This may suggest that these changes may be reflected by enzyme activity in the serum. Therefore, we have measured the activity of total ADH, and classes I-IV of this enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 14 publications
2
32
0
2
Order By: Relevance
“…A lot of enzymes in cancer cells may change their activity. It is commonly accepted that changes of enzyme activity in the neoplastic tissue are reflected by increase of the corresponding enzyme activity in the serum [14,15]. In our last study, we found that alcohol dehydrogenase isoenzymes and aldehyde dehydrogenase are present in esophageal cancer cells.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A lot of enzymes in cancer cells may change their activity. It is commonly accepted that changes of enzyme activity in the neoplastic tissue are reflected by increase of the corresponding enzyme activity in the serum [14,15]. In our last study, we found that alcohol dehydrogenase isoenzymes and aldehyde dehydrogenase are present in esophageal cancer cells.…”
Section: Discussionsupporting
confidence: 53%
“…For example, in colorectal cancer the total activity of alcohol dehydrogenase and the class I of ADH (the principal class of ADH isoenzymes in the colon) were significantly higher than in healthy colon mucosa [9]. Therefore, the activity of class I alcohol dehydrogenase isoenzymes was significantly elevated in the serum of patients with colorectal cancer [15]. In pancreatic cancer, the activity of class III ADH is significantly higher in Table 3 The activity of ADH isoenzymes and ALDH in the serum of drinkers and non-drinkers with esophageal cancer cancer tissues and the activity of this class is significantly higher in the serum of patients with pancreatic cancer than in the healthy group [20,21].…”
Section: Discussionmentioning
confidence: 98%
“…In particular, ALDH bright cells from human umbilical cord blood and peripheral blood leukemic stem cells have been shown to contain all the nonobese diabetic/SCID engrafting cells in CD34 + cells (18,19). In addition, recent research efforts have shown that ALDH is highly expressed in non -small-cell lung, colon, and pancreatic cancers (20)(21)(22), and that higher ALDH activity levels can be used to better identify the colon CSC population with EpCAM high CD44 + phenotype (6), as well as the glioblastoma (23), retinoblastoma (24), and breast (25) CSC populations. In view of these recent advances, it was both reasonable and logical to speculate that ALDH1A1 or the more general ALDH may possibly play an important role in the better characterization of CD133 + HCC CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The total ADH activity has been elevated in the sera of patients with colorectal cancer. The increase of total ADH activity was positively correlated with class I ADH and seems to be caused by the release of this isoenzyme from cancer cells [5].…”
Section: Introductionmentioning
confidence: 88%